The logical foundations of constitutional democracy between legal positivism and natural law theory - Hartmut Kliemt (Public Choice, 2021)
Rejecting all knowledge claims concerning right and wrong in matters practical James Buchanan concurred with legal positivism that invalid law cannot be identified by its substantive content but only by an inherited defect in its factual creation. Beyond correct creation Buchanan proposed as a quasi-natural law constraint that unanimity in the shadow of individual veto power must at least be conceivable if a norm is to be law. The emerging hybrid conception of constitutional law is symptomatic for Buchanan's never-ending but ultimately futile efforts to incorporate Kantian ideals of interpersonal respect into constitutional economics without imposing them as personal values.
Keywords: 330; Buchanan; Kant; Kelsen; Rule of law; Legal positivism; Natural law